A case of myotonic dystrophy type 1 with paternal history of clinical worsening - S. A. Kurbatov; V. P. Fedotov; N. M. Galeeva; V. V. Zabnenkova; A. V. Polyakov (Анналы клинической и экспериментальной неврологии, 2017)
Myotonic dystrophy type 1 (DM1) is an autosomal dominantdisease associated with the expansion of trinucleotide CTG repeatsin the dystrophia myotonica protein kinase (DMPK) gene.DM1 is clinically manifested by a combination of myotonia,progressive atrophy of skeletal muscles, and the multisystemiccharacter of the disorder, severity of which correlates with theCTG tract length. DM1 is characterized by anticipation that ismanifested in the worsening and more early onset of the diseasein each succeeding generation, especially when inherited fromclinically affected mothers. Using clinical observation of a familywith two cases of advansed DM1 forms as an example, it wasdemonstrated that clinical, electromyographic, and moleculargenetic examinations of all first-degree relatives (parents, siblings,children) are required for the correct prognosis and geneticcounseling.